Simultaneous Relationship Analysis Between Carbon Dioxide Emissions and GDP Per Capita in Asia: The Dynamics of Urbanization, Energy Consumption, Foreign Direct Investment, and Trade Openness - Kamil Habibi; Imam Asngari; Abdul Bashir; Azwardi; Muhammad Subardin (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the simultaneous relationship between carbon dioxide (CO₂) emissions and GDP per capita in 10 Asian countries, considering the dynamics of urbanization, energy consumption, foreign direct investment (FDI), and trade openness. The research employs an explanatory quantitative approach using panel data covering the period 2000–2024, obtained from the World Bank (WDI). The analysis applies a simultaneous equation model estimated using the Two Stage Least Squares (2SLS) method to address endogeneity issues. The results indicate that CO₂ emissions are significantly influenced by GDP per capita, urbanization, energy consumption, FDI, and lagged emissions, highlighting the presence of persistence effects. Meanwhile, GDP per capita is significantly affected by CO₂ emissions, FDI, and its lagged value. These findings suggest that economic growth in Asia remains highly dependent on energy-intensive and investment-driven activities, characterized by strong path dependence. Overall, the relationship between economic growth and environmental degradation is found to be mutually interdependent within a simultaneous system.